Pleural mesothelioma and asbestos exposure among Italian oil refinery workers. - Gennaro, Valerio; Ceppi, Marcello; Boffetta, Paolo; Fontana, V; Perrotta, A (Scandinavian Journal of Work, Environment & Health, 1994)
OBJECTIVES--The association between asbestos exposure and risk of mesothelioma was studied among workers from two oil refineries located in the northern Italian cities of Genoa and La Spezia, given that previous cohort analyses revealed two clusters of mesotheliomas and that international cohort studies have so far not reported an excess of this neoplasm among oil refinery workers. METHODS--Men (N = 2300) who had been employed between 1914 and 1988 in two oil refineries located in northern Italy were studied. The follow-up covered the mortality of 639 white-collar and 1661 blue-collar from 1950 to 1991. RESULTS--Among the cases, the median duration of employment was 14.5 years, and the median time since first employment was 27.5 years. The job titles of the 10 men with pleural mesothelioma were maintenance worker (seven men), electrician (one man) and unspecified blue-collar worker (two men). Blue-collar workers experienced a significantly increased risk of pleural neoplasms, five deaths in each plant, in respect to both the provincial [standardized mortality ratio (SMR) 266] and national (SMR 1663) reference populations. The SMR, based on eight deaths, was 320 for workers with more than 10 years of employment and 20 years since first exposure. CONCLUSIONS--The results uphold the notion that exposure to asbestos in oil refineries causes pleural mesotheliomas. This is the first study to find an excess of pleural mesotheliomas among oil refinery workers exposed to asbestos.